Respuesta :

[tex]\bf\huge Question:[/tex]

[tex]4c-3x=2y - 3[/tex]

We need to find the value of c in the given Equation.

[tex]\bf\huge \: Solution:[/tex]

[tex] \sf \longmapsto \: 4c-3x=2y - 3[/tex]

[tex] \boxed{\bf Add \: 3x \: to \: both \: sides:}[/tex]

[tex]\sf \longmapsto \: 4c - 3x + \red{ 3x} = 2y - 3 + \red{ 3x}[/tex]

[tex] \underline{\bf \: \bf On \:Simplification :}[/tex]

[tex]\sf \longmapsto \: 4c = 2y - 3 + 3x[/tex]

[tex]\sf \longmapsto4c = 3x + 2y - 3[/tex]

[tex] \boxed{\bf \: Divide \: both \: side s \: by \: 4 :} [/tex]

[tex]\sf \longmapsto \: \dfrac{4c}{ \red4} = \dfrac{3x + 2y - 3}{ \red4} [/tex]

[tex]\underline{ \bf \: \bf On \:Simplification :}[/tex]

[tex] \sf \longmapsto \: c = \dfrac{3}{4} x + \dfrac{1}{2} y + \dfrac{ - 3}{4} [/tex]

______________________________________

[tex] \underline{\bf \: Henceforth, The \: value \: of \: c \: is :} [/tex]

[tex] \boxed{\red{\huge \tt{{c}}= \dfrac{3}{4} x + \dfrac{1}{2} y + \dfrac{ - 3}{4} }}[/tex]

Or it can also be rewritten as :

[tex] \boxed{\red{\huge \tt \: c = \dfrac{1}{2} y - \dfrac{3}{4} + \dfrac{3}{4} x}}[/tex]

ACCESS MORE